APOSTASY AND MARRIAGE DISSOLUTION IN INDONESIA: A CRITICAL ANALYSIS OF JUDICIAL REASONING IN RELIGIOUS COURT DECISION NO. 7938/PDT.G/2020/PA.SOR - Rizky Kurniawan; Isnain La Harisi (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to analyze the dissolution of marriage due to apostasy in the practice of religious courts in Indonesia through a case study of the Soreang Religious Court Decision Number 7938/Pdt.G/2020/PA.Sor. This research employs a normative juridical method with statutory, conceptual, and case approaches. The findings reveal that the dissolution of marriage due to religious conversion is carried out through the mechanism of fasakh, with the Compilation of Islamic Law serving as the primary legal basis, despite the absence of explicit regulation in Law Number 1 of 1974 on Marriage. Judges apply an interpretative approach by linking apostasy to marital disharmony, reflecting the active role of religious courts in addressing legal gaps and harmonizing Islamic law with national law. From a theoretical perspective, the findings highlight the tension between legal certainty and substantive justice (legal certainty versus justice tension) and emphasize the relevance of procedural justice theory in assessing judicial decisions. From the perspective of Islamic law, differences exist among schools of thought regarding the mechanism of marital dissolution due to apostasy; however, Indonesian practice tends to adopt a judicial approach requiring court decisions. Practically, this study identifies the potential for inconsistent rulings due to the absence of explicit legal norms and standardized guidelines. Therefore, this study recommends revising the Marriage Law and establishing judicial guidelines by the Supreme Court to enhance legal certainty and consistency in similar cases.